LncRNA GAS5 controls cardiac fibroblast activation and fibrosis by targeting miR-21 via PTEN/MMP-2 signaling pathway. (1st July 2017) - Tao, Hui; Zhang, Jia-Gui; Qin, Run-He; Dai, Chen; Shi, Peng; Yang, Jing-Jing; Deng, Zi-Yu; Shi, Kai-Hu
Highlights: LncRNA GAS5 plays a key role in CFs activation and fibrosis. GAS5/miR-21/PTEN axis involvement in CFs activation. GAS5 negative controls miR-21 expression in activated CFs. Abstract: Long noncoding RNAs (LncRNAs) are aberrantly expressed in many diseases including cardiac fibrosis. LncRNA growth arrest-specific 5 (GAS5) is reported as a significant mediator in the control of cell proliferation and growth; however, the role and function in cardiac fibrosis remain unknown. In this study, we confirmed that GAS5 was lowly expressed in cardiac fibrosis tissues as well as activated cardiac fibroblast. Overexpression of GAS5 inhibited the proliferation of cardiac fibroblast. Moreover, microRNA-21 (miR-21) has been reported to be overexpressed in cardiac fibrosis tissues as well as activated cardiac fibroblast, which is responsible for the progression of cardiac fibrosis. We found that up-regulated GAS5 decreased the expression of miR-21 significantly. Furthermore, GAS5 that upregulated or downregulated the expression of PTEN through miR-21 in cardiac fibroblasts. Taken together, GAS5 plays a suppressive role in cardiac fibrosis via negative regulation of miR-21. These results indicated that GAS5 may be a novel therapeutic target for further research of cardiac fibrosis.